Tumor necrosis factor in acute leukemia patients - Prymak, S.V.; Matlan, V.L.; Barilka, V.A.; Shalay, O.O.; Loginsky, V.E. (Онкологія, 2015)
Aim: to study the tumor necrosis factor (TNF) concentration in blood plasma of the patients with acute leukemia (AL), its production by the primary culture of peripheral blood mononuclear cells (PBMC) and to estimate the relation between these rates and hematologic signs of the AL. Material and methods: the TNF concentration in blood plasma of 44 patients with AL was studied applying biological method based on its cytolytic effect in TNF-sensitive culture of L929 line transformed mouse fibroblasts estimated by radiometric method. Results: TNF concentration in blood plasma of the patients with AL is significantly higher than normal value, and its production by the PBMC increases too. But the TNF fraction produced by PBMC in TNF plasma concentration (Index I) is smaller than in healthy persons. Anemia and thrombocytopenia are accompanied by the increase of TNF concentration in blood plasma, as well as its production by PBMC. Conclusions: the results make it possible to consider the increase of TNF level in AL as a proapoptotic manifestation of changes in hematopoiesis which results in the development of anemia and thrombocytopenia.